2020
DOI: 10.1111/1750-3841.15485
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration isolation, physicochemical characterization, and antidiabetic activities analysis of polysaccharides from green tea, oolong tea, and black tea

Abstract: Both fermentation degree and preparation method of polysaccharides could influence the bioactivity of tea polysaccharides. The aim of this study was to compare the physicochemical characterization and biological activities of the polysaccharides isolated by ultrafiltration method from three kinds of tea (green tea, oolong tea, and black tea). The bioactivities of tea polysaccharide fractions were compared from four aspects, including antioxidant activities, antiglycation activities, α‐glucosidase inhibitory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…Similarly, a significant positive correlation was found between GAC and the fucose or uronic acid content, a strong positive correlation was observed between GAC and arabinose or galactose, and a significant positive correlation was presented between GC and the uronic acid content. Previous studies have shown that TPS with relatively low molecular weights exhibited better bioactivities [56], and the findings of the current study were consistent with those of Xu, who found TPS with a small Mw showed better bioactivity, including lowering the blood glucose and antioxidation [57]. Additionally, the high content of uronic acid in polysaccharides has also been pointed out to have bioactivity [58,59].…”
Section: In Vitro Hypoglycemic Activities Of Dtpsssupporting
confidence: 91%
“…Similarly, a significant positive correlation was found between GAC and the fucose or uronic acid content, a strong positive correlation was observed between GAC and arabinose or galactose, and a significant positive correlation was presented between GC and the uronic acid content. Previous studies have shown that TPS with relatively low molecular weights exhibited better bioactivities [56], and the findings of the current study were consistent with those of Xu, who found TPS with a small Mw showed better bioactivity, including lowering the blood glucose and antioxidation [57]. Additionally, the high content of uronic acid in polysaccharides has also been pointed out to have bioactivity [58,59].…”
Section: In Vitro Hypoglycemic Activities Of Dtpsssupporting
confidence: 91%
“…Studies have shown that different varieties, production areas, tea-making techniques, the growth position of the leaves on the tea tree, and the age of the tea tree will affect the content, physical and chemical properties and biological activity (Yang et al, 2010) of tea polysaccharides, even if the same tea raw materials use different tea polysaccharide extraction methods, the extraction rate, physical and chemical properties, and biological activity will be different (Qin et al, 2021;Xu et al, 2020;Zhang et al, 2016;Zhu, Yu, et al, 2020). In short, the extraction rate, physical and chemical properties, and biological activity of tea polysaccharides are affected by many aspects.…”
Section: The Optimization Of Extraction Methodsmentioning
confidence: 99%
“…The intrinsic viscosities of the four OTPS components were 239.56, 162.63, 7.75, and 2.57 mL/g, respectively, which indicated that their intrinsic viscosities increased with relative decreases in Mw. Xu et al, isolated and purified six TPS components with different Mw values from green, oolong, and black teas, and then they performed an intrinsic viscosity analysis [ 76 ]. The Mw values of GTPS1, OTPS1, and BTPS1 were less than 80 kDa, while the Mw values of GTPS2, OTPS2, and BTPS2 were greater than 80 kDa.…”
Section: Preliminary Physicochemical Properties Of Tpsmentioning
confidence: 99%
“…Additionally, the inhibitory activities of GTPS1 and GTPS2 against α-glucosidase were weaker than those of other TPS fractions, results consistent with those of Chen et al, In addition to the type of tea, the degree of fermentation of tea can also affect its glycosidase inhibitory activity. The aging (light fermentation) process was found to significantly enhance the antioxidant and α-glucosidase inhibitory activities of Pu-erh TPS [ 76 ]. Xu et al, extracted three TPSs (PTPS-1, PTPS-3, and PTPS-5) from Pu-erh tea with different fermentation years (first, third, and fifth) and then tested their α-glucosidase inhibitory activity [ 36 ].…”
Section: In Vitro Bioactivity Of Tpsmentioning
confidence: 99%
See 1 more Smart Citation